DESIGNING AND EFFICIENCY EFFECT OF AUTOMATIC BALL-CLEANING SYSTEM FOR CONDENSER 180-KTsS-1 OF TURBINE Т-180/210-130-1 LMZ. Part 2 - Yu. A. Zenovich-Leshkevich-Ol’pinskiy; A. Yu. Naumov; A. Yu. Zenovich-Leshkevich-Ol’pinskaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The authors elaborate the economical efficiency evaluation technique that could be universal and applied for technical-and-economic feasibility study of the ball-cleaning system installation on the steam turbines of the electric power plants. Besides the effect from reducing the exhaust steam pressure in the condenser by means of the ball-cleaning system implementation, this technique also accounts for the effect of lowering the condenser hydraulic pressure.The article refers to the practical results of the ball-cleaning system introduction on the steam turbines of Gomel CHP-2. As a result of regular application of the ball-cleaning system the temperature difference of the condensers of all blocks Т-180/210-130-1 confined into the regulatory values and the cleanness coefficient of all three turbine units reached 0,85. The authors consider the working results, implementation experience of the ball-cleaning system at Gomel CHP-2 and its efficiency evaluation technique to be worth disseminating when introducing the analogous systems at the plants of Belarusian power network.The authors suggest measures on the condenser automatic-cleaning system improvement with the turbine mathematical-simulation model employment that will make it possible to optimize the condenser cleaning regimes and to increase the ball-cleaning system effectiveness with the condenser cleanness coefficient growing up to 0,90–0,92.